Passive Transfer of Immunity and Serum Proteinogram during the First 35 Days of Age in Nelore Calves Conceived Naturally or Through In Vitro Fertilization - Lisbôa, Júlio Augusto Naylor; Sturion, Tiago Torrecillas; Anjos, Mayara Cardoso dos; Flaiban, Karina Keller Marques da Costa (Acta Scientiae Veterinariae, 2016)
Background: Some reports indicate that calves produced by in vitro fertilization (IVF) may have excessive birth weights, increasing the rates of dystocia. Prolonged labor can cause the birth of lethargic calves that slowly ingest colostrum; this may compromise the intestinal absorption of immunoglobulins. Although the number of beef calves produced by IVF is high in Brazil, there have been few physiological studies examining the neonatal period in such cases. The aim of this study was to evaluate the passive transfer of immunity, and characterize the variation in serum protein concentrations, in Nelore calves up to 35 days of age, comparing naturally conceived calves with those conceived by IVF. Materials, Methods & Results: Forty healthy newborn Nelore calves were randomly selected and allocated into two groups (n = 20) according to their method of conception (natural versus IVF), and each group was composed of ten males and ten females. All calves were born and raised on the same farm, and kept with their mothers on extensive management condition. Blood samples were collected between 24 and 36 h after birth, and at 7, 14, 21, 28, and 35 days of age. Total protein (TP) concentration in serum was measured by the biuret method, and gamma-glutamyl transferase (GGT) serum activity was measured by the kinetic method. Concentrations of serum albumin, as well as alpha 1-, alpha 2-, beta, and gamma globulins were measured by agarose gel electrophoresis. Serum immunoglobulin G (IgG) concentration was estimated by the zinc sulfate turbidity test. The effects of sex, age, and conception method, on aforementioned serum parameters, were tested by repeated measures ANOVA. Sex of calves did not affect the studied variables (P > 0.05) and there was no interaction between the age and the conception method (P > 0.05). Naturally conceived calves presented higher TP and IgG concentrations (P < 0.05), and lower concentrations of alpha 1- and alpha 2-globulins (P < 0.05), than that of those conceived by IVF. Age exerted greater influence on the serum parameters in the two groups. Serum concentrations of TP (P < 0.05), beta globulin (P < 0.05), gamma globulin (P < 0.001), IgG (P < 0.01), and globulins (P < 0.001), as well as serum activity of GGT (P < 0.0001) were high at 24 to 36 h after birth, and decreased with age. Albumin concentration, however, increased (P < 0.01) in the first weeks of life. The variation in alfa 2-globulin concentration was discrete (P < 0.05), and the serum concentration of alfa 1-globulin did not change (P > 0.05) with age. These patterns of variation related to age were observed in both groups with no apparent distinctions. Based on values obtained at 24 to 36 h after birth, it can be asserted that the passive transfer of immunity was successful in both groups, despite the differences in total protein and IgG concentrations. Discussion: The age-related variations in serum proteinogram components over the first 35 days of age may be considered physiological; and were consistent with previous studies in healthy Nelore calves. These were characterized by gradual decreases in TP, gamma globulins, IgG, and globulin concentrations, as well as GGT activity, and by increase in albumin concentration. The results do not corroborate the suspicion that calves conceived by IVF are more prone to failure of passive transfer. It can be concluded that Nelore newborn calves conceived through IVF, having standard weight at birth, do not have physiological differences related to serum protein concentrations when compared to calves conceived by natural methods.